Diagnostic challenges: low-grade adenosarcoma on deep endometriosis - Jose Carlos Vilches Jimenez; Emilia Villegas Muñoz; Iván González Poveda; David Santos Lorente; Belinda Sanchez Pérez; Jesús S. Jimenez Lopez (BMC, 2019)
Abstract Background Müllerian adenosarcoma is a rare malignancy. These tumors occur mainly in the uterus, but also in extrauterine locations, usually related to endometriosis. Because of their rarity, there is limited data on optimal management strategies. Case presentation We present a 44-year-old woman with a history of endometriosis who consults for chronic pelvic pain. In the imaging tests, a heterogeneous mass is observed that impresses endometriosis, encompassing the uterus and left appendage. Surgery is performed by finding an extrauterine adenosarcoma that affected the uterus, ovary and bladder wall. Conclusion This is a rare case but should be considered in a patient with atypical clinical characteristics or preoperative pathology, so we show the diagnostic and therapeutic strategies carried out for the resolution of the case.